Nixtric oxide detection using Wavelength modulation spectroscopy and its application in breath and cell death diagnostics - Mitrayana, .; Pierera, T.; Cristescu, S.M.; Harren, F.J.M.; Wasono, M.A.J.; Rochmah, W. (2009)
We used a thermoelectrically cooled, continous-wave, quantum cascade laser operating between 1891.3 and 1907.6 1/cm in combination with wavelength modulation spectroscopy for the detection of nitric oxide at sub-part-per-billion volume (ppbv). The laser emission overlaps with the P7,5 double of NO centered around 1903,9 1/cm. Using as astigmatic multiple pass absorption cell with an optical path length of 76 m we achieved a detection limit of 0.8 ppbv at 100 mbar. with a total acquisition time of 30 seconds. The corresponding minimal detectable absorption is 3.5 x 10(-10) 1/cm/Hz(-1/2). We used that detector to detect the concentration of NO gas from the sample air from the breath and algae cell-death.